2008
DOI: 10.1111/j.1365-2656.2008.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of extinction in experimental populations

Abstract: Summary 1.Population extinction is a fundamental ecological process. Recent experimental work has begun to test the large body of theory that predicts how demographic, genetic and environmental factors influence extinction risk. We review empirical studies of extinction conducted under controlled laboratory conditions. Our synthesis highlights four findings.First, extinction theory largely considers individual, isolated populations. However, species interactions frequently altered or even reversed the influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 102 publications
2
51
0
1
Order By: Relevance
“…By increasing the intensity of the Poisson distribution of offspring per reproducing couple from 2 to 3, populations almost never went extinct (electronic supplementary material, figure S12). This result shows how a moderate increase in fecundity may have substantial effects on the survival of populations in highly stochastic environments, as also suggested by theoretical [29] and experimental [58] studies, although trade-offs with survival and other life histories should be considered [59]. This might explain why fecundity is strongly selected under environmental change in long running experimental populations [60,61], although whether this is caused by environmental variation or environmental trend is unclear.…”
Section: Additive Genetic Variance and Prediction Of Contemporary Rissupporting
confidence: 62%
“…By increasing the intensity of the Poisson distribution of offspring per reproducing couple from 2 to 3, populations almost never went extinct (electronic supplementary material, figure S12). This result shows how a moderate increase in fecundity may have substantial effects on the survival of populations in highly stochastic environments, as also suggested by theoretical [29] and experimental [58] studies, although trade-offs with survival and other life histories should be considered [59]. This might explain why fecundity is strongly selected under environmental change in long running experimental populations [60,61], although whether this is caused by environmental variation or environmental trend is unclear.…”
Section: Additive Genetic Variance and Prediction Of Contemporary Rissupporting
confidence: 62%
“…Power lines may influence wildlife through disturbance, clearing of forest habitat under power lines, edge, barrier and corridor effects (Willyard and Tikalsky, 2004;Ball, 2012). Fragmentation by power lines could induce genetic drift, as for roads (Epps et al, 2005, Kuehn et al, 2007, and reduce population productivity and persistence (Griffen and Drake 2008;Haanes et al, 2013). Wide-ranging and mobile species as some ungulates will likely encounter power lines within their home ranges (Tables 1 to 7).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the different mechanisms by which small populations may affect extinction risk has been controversial. Attention has increasingly focused on the effects of genetic factors (Franklin 1980, Barrett and Kohn 1991, Lacy 1997, Frankham 2005, Bouzat 2010, Miller et al 2012, in part because of well-documented effects of inbreeding in captive populations, including those of conservation interest in zoos (Charlesworth and Charlesworth 1987, Lacy 1997, O'Brien 1994, Griffen and Drake 2008, and because rapid improvements in DNA analysis has facilitated assessment of genetic structure in small populations. Some biologists have questioned this emphasis, and suggested that nongenetic factors such as demographic stochasticity and environmental factors that cause small population size have overriding importance in natural populations (Simberloff 1988, Caughley 1994, Caro and Laurenson 1994.…”
Section: Introductionmentioning
confidence: 99%